Effects of Satisfaction on Pimpiang Alahan Panjang Island Tourism Visitors - Rasidah Nasrah; Ida Nirwana; Lili Nur Indah Sari (LPPM STIE EKA PRASETYA, 2024)
This research was conducted at Pimpiang Alahan Panjang Island Tourism, Solok Regency. The study aims to determine how big the effect of visitor satisfaction is on Pimpiang Alahan Panjang Island Tourism, Solok Regency. The population used was 50 visitors to Pimpiang Island tourism. By using the sampling technique, namely the Accidental Sampling method. Questionnaires are data collection techniques. Based on multiple regression analysis, the variables Location (X1) and Facilities (X2) affect Visitor Satisfaction (Y). The multiple linear regression equation obtained is Y = 1.358 + 0.827 (X1) + 0.158 (X2) + 0.05. The coefficient of determination shows that the independent variables (X1 and X2) have an influence of 70.7% on the dependent variable (Y), while the remaining 29.3% is influenced by other variables not included in the study. The t-test of the variables Location (X1) and Facilities (X2) shows that both have a significant effect on Visitor Satisfaction (Y) with f count > f table. From the f test, Location (X1) Facilities (X2) simultaneously or together have a significant influence on the dependent variable, namely Visitor Satisfaction (Y), the calculated f value > f table (56.757 > 3.18) and the sign level is <0.05 (0.000 <0.05).